A critical review and meta-analysis of the unconscious thought effect in medical decision making - Vadillo, Miguel A.; Kostopoulou, Olga; Shanks, David R. (Frontiers in Psychology, 2015)
Based on research on the increasingly popular unconscious thought effect (UTE), it has been suggested that physicians might make better diagnostic decisions after a period of distraction than after an equivalent amount of time of conscious deliberation. However, published attempts to demonstrate the UTE in medical decision making have yielded inconsistent results. In the present study, we report the results of a meta-analysis of all the available evidence on the UTE in medical decisions made by expert and novice clinicians. The meta-analysis failed to find a significant contribution of unconscious thought to the accuracy of medical decisions. This result cannot be easily attributed to any of the potential moderators of the UTE that have been discussed in the literature. Furthermore, a Bayes Factor analysis shows that most experimental conditions provide positive support for the null hypothesis, suggesting that these null results do not reflect a simple lack of statistical power. We suggest ways in which new studies could usefully provide further evidence on the UTE. Unless future research shows otherwise, the recommendation of using unconscious thought to improve medical decisions lacks empirical support.